The Effect of Cognitive Behavioral Group Therapy on Sense of Belonging and Depression in First-Year University Students: A Pilot Randomized Controlled Trial - Bonnie Bozorg; Zahra Rafati; Mina Bozorg (Journal of Educational, Health and Community Psychology, 2026)
A strong sense of belonging is associated with better psychological adjustment and academic functioning among university students, whereas low belongingness is linked to depressive symptoms, particularly during the first year of university. Evidence on group-based psychological interventions targeting belongingness in depressed first-year students remains limited. This study examined the effectiveness of cognitive behavioral group therapy (CBGT) on sense of belonging and depressive symptoms in first-year university students diagnosed with major depressive disorder (MDD). This single-assessor-blinded, parallel-group pilot randomized controlled trial was conducted between September and December 2023 at the mental health service of a public medical university in Iran. Twenty first-year students with MDD were randomly assigned to CBGT (n = 10) or treatment as usual (TAU; n = 10). The CBGT group received eight weekly sessions in addition to routine care, while the TAU group received routine care only. Outcomes were assessed at baseline, post-treatment, and 1- month follow-up using the Sense of Belonging Instrument (SOBI) and the Beck Depression Inventory–II (BDI-II). The SoB in the CBGT group increased significantly compared to that in the control group after treatment (p = .001). After treatment, the BDI scores in the control group were much greater than those in the treatment group (21.07 vs. 16.86, p = .001). Both variables were much more effective in the CBGT group than in the control group (p = .001). CBGT appears to be a feasible and effective intervention for improving sense of belonging and reducing depressive symptoms among first-year university students with MDD. Larger, fully powered trials with longer follow-up periods are warranted.